(untitled) (Research, Society and Development, 2020)
This article aims to provoke reflections on scientific activity and the non-neutrality of science, based on Hugh Lacey’s theoretical perspective as an epistemological foundation. Contemplating their perceptions about values and scientific activity, the perspectives that perpetuate in contemporary science practices stand out, as well as the modern values of controls that predominate in the scientific field. Methodologically, this research is classified as bibliographic, descriptive and qualitative. The results obtained emphasize the methodological pluralism defended by the author as a necessary principle for the neutrality of science since his theory is based on the assumption that there is a dialectical relationship between science, scientific activity and human well-being. It also highlights the need for science teaching to be practiced from a critical reflexive perspective, without being relativistic since science is a socio-historical practice inserted in the world of values and human experience, undertaken by agents human beings, whose actions are explainable in terms of their beliefs, perceptions, deliberations, desires, values and other intentional opportunities.